Anti-Tumor Necrosis Factor α Therapeutics Differentially Affect Leishmania Infection of Human Macrophages - Arens, Katharina; Filippis, Christodoulos; Kleinfelder, Helen; Goetzee, Arthur; Reichmann, Gabriele; Crauwels, Peter; Waibler, Zoe; Bagola, Katrin; van Zandbergen, Ger (Frontiers in Immunology, 2018)
Tumor necrosis factor α (TNFα) drives the pathophysiology of human autoimmune diseases and consequently, neutralizing antibodies (Abs) or Ab-derived molecules directed against TNFα are essential therapeutics. As treatment with several TNFα blockers has been reported to entail a higher risk of infectious diseases such as leishmaniasis, we established an in vitro model based on Leishmania-infected human macrophages, co-cultured with autologous T-cells, for the analysis and comparison of anti-TNFα therapeutics. We demonstrate that neutralization of soluble TNFα (sTNFα) by the anti-TNFα Abs Humira®, Remicade® and its biosimilar Remsima® negatively affects infection as treatment with these agents significantly reduces Leishmania-induced T-cell proliferation and increases the number of infected macrophages. In contrast, we show that blockade of sTNFα by Cimzia® does not affect T-cell proliferation and infection rates. Moreover, compared to Remicade®, treatment with Cimzia® does not impair the expression of cytolytic effector proteins in proliferating T-cells. Our data demonstrate that Cimzia® supports parasite control through its conjugated polyethylene glycol (PEG) moiety as PEGylation of Remicade® improves the clearance of intracellular Leishmania. This effect can be linked to complement activation, with levels of complement component C5a being increased upon treatment with Cimzia® or a PEGylated form of Remicade®. Taken together, we provide an in vitro model of human leishmaniasis that allows direct comparison of different anti-TNFα agents. Our results enhance the understanding of the efficacy and adverse effects of TNFα blockers and they contribute to evaluate anti-TNFα therapy for patients living in countries with a high prevalence of leishmaniasis.